High-Resistance Connection Diagnosis Considering Current Closed-Loop Effect for Permanent Magnet Machine - Xu, Zheng; Din, Zakiud; Jiang, Yongjiang; Cheema, Khalid Mehmood; Milyani, Ahmad H.; Alghamdi, Sultan (Frontiers in Energy Research, 2022)
The permanent magnet (PM) machine has been widely applied in the area of wind power and electric vehicles. As one of the most common electric faults, high-resistance connection (HRC) will induce 2nd-order components in the dq-axis current and voltage, which can be used for HRC diagnosis. However, these HRC-introduced 2nd-order components are also affected by the current closed-loop control, which ought to be taken into consideration for an accurate HRC diagnosis. In this paper, a mathematical model of the 2nd-order components in the dq-axis current and voltage for the current closed-loop controlled PM machine is derived, based on which a new HRC diagnosis method is proposed. In the proposed method, not only the location of HRC but also the HRC severity can be accurately obtained. Simulations and experiments have been carried out to validate the effectiveness of the proposed method.